Nutritive Value of Fish Waste Silage Meal - , Nithya. G; , R. Suresh (Archives of Current Research International, 2025)
The Fish Waste Silage Meal (FWSM) was prepared using fish offals, Lactobacillus plantarum culture (108 cfu/ml), jaggery and De-Oiled Rice Bran (DORB). Fish waste silage (FWS) was prepared by incubating minced and autoclaved fish offal slurry with 10 percent jaggery and 5 percent Lactobacillus plantarum culture (108 cfu/ml) in an anaerobic condition for 14 days at room temperature (37°C) with occasional mixing. After the fermentation period, the FWS was mixed with DORB (Slurry: DORB, 7:1) uniformly and sun-dried for 3-4 days for the production of FWSM, 0.72 kg FWSM was produced from 1.0 kg of FWS. The FWSM was analysed for its nutritive value, the FWSM contains 10.8% moisture, 27.5% crude protein (CP), 4.97% crude fiber, 14.01% ether extract and 17.09% total ash. Since FWSM is prepared from inedible parts of the fish; FWSM was screened for major pathogenic microorganisms’ viz., E. coli, Salmonella and Clostridium and found negative. Further, FWSM is analyzed for five common mycotoxins (Aflatoxin (B1, B2, G1 and G2), Ochratoxin, T-2 toxin, Citrinin and Zearalenone) and found negative. The transformation of fish waste into FWSM not only produces a highly nutritious end product but also offers an alternative and beneficial means of utilization. The FWSM contains 27.5% CP, which is almost equal to the 50% CP value of soybean meal, thus it can be used as a feed ingredient in animal feed preparation.